Diagnostic and therapeutic process of respiratory disorders during sleep - Maliszewska, Karolina; Oleksak, Izabela; Welian-Polus, Iwona; Gendek, Karolina; Wilanowska, Wiktoria; Babkiewicz-Jahn, Kamila; Matuszewska, Justyna (Journal of Education, Health and Sport, 2024)
Introduction and purpose Sleep apnea is a disturbance of sleep that affects about 10% of adult population and is not easily detected due to unspecific symptoms. The aim of this literature review is to present, respectively, obstructive sleep apnea and central sleep apnea symptoms and integrate the available data in the literature regarding the pathogenesis and treatment methods. Materials and methods A review of literature was performed using PubMed and Google Scholar database. The search criteria included keywords such as sleep apnea, obstructive sleep apnea treatment, central sleep apnea treatment. State of knowledge Sleep disturbances that involve breathing can be categorized as obstructive sleep apnea (OSA) and central sleep apnea. First one is associated with the obstruction of the upper airways and the second one – with malfunctioning breathing generator in the pontomedullary breathing pacemaker. Symptoms are unspecific which makes diagnostic process difficult. However, the right diagnosis and treatment may prevent patients from developing many cardiovascular diseases. Treatment options for OSA include: CPAP, reducing body weight, changing sleep position, braces and surgeries; for CSA: CPAP and acetazolamide. Conclusions OSA and CSA need to be further investigated in order to find more precise ways of diagnosis and treatment, as these diseases remain underreported. It is worth noting, that these conditions predispose to serious diseases, e.g. stroke. Therefore, developing new treatment techniques would beneficial for the health of population.